The treatment of pseudoaneurysms with flow diverters after malignant otitis externa - Németh Tamás; Szakács László; Bella Zsolt; Majoros Valéria; Barzó Pál; Vörös Erika Sarolta (2017)
Background We report a case of bilateral malignant otitis externa complicated with bilateral petrous internal carotid artery pseudoaneurysms and their successful treatment with a flow diverter. Case report A 68-year-old woman with serious complications of type II diabetes mellitus had malignant otitis externa on the right side. She was treated with combined antibiotic therapy and underwent mastoidectomy for mastoiditis. She presented at our hospital with acute hemorrhage from the right external auditory canal. The emergency computed tomography (CT) angiography revealed a multiobulated pseudoaneurysm at the petrous segment of the right internal carotid artery. The pseudoaneurysm was treated with a 5 x 40-mm Surpass flow diverter. Three months later, she developed a malignant external otitis on the left side. As the infection progressed, a left-sided mastoiditis, a brain abscess, and a pseudoaneurysm at the petrous segment of the left internal carotid artery developed. The pseudoaneurysm caused bleeding from the left ear, and was treated with a 5 x 50-mm Surpass flow diverter. No recurrent bleeding was observed. Four months later, a follow-up angiography showed complete occlusion of the pseudoaneurysm on the left side, but a residual aneurysm could be detected on the right side. One year after the first intervention, the follow-up CT and magnetic resonance angiography revealed the complete occlusion of the aneurysms bilaterally. Conclusion The use of a flow diverter appears to be an efficient and safe method to occlude carotid pseudoaneurysms even in an inflammatory milieu.